2023
DOI: 10.3390/ijms24087608
|View full text |Cite
|
Sign up to set email alerts
|

MTX-211 Inhibits GSH Synthesis through Keap1/NRF2/GCLM Axis and Exerts Antitumor Effects in Bladder Cancer

Abstract: Globally, bladder cancer (BLCA) is still the leading cause of death in patients with tumors. The function and underlying mechanism of MTX-211, an EFGR and PI3K kinase inhibitor, have not been elucidated. This study examined the function of MTX-211 in BLCA cells using in vitro and in vivo assays. RNA sequencing, quantitative real-time polymerase chain reaction, Western blotting, co-immunoprecipitation, and immunofluorescence were performed to elucidate the underlying mechanism. Our observations revealed that MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…In the present study, our objective was to assess the influence of ABCG2 on the anti-proliferative efficacy of MTX-211. We observed that MTX-211 displayed inhibitory effects on cancer cell proliferation across various origins, with IC50 values falling within the range of approximately 1-8 µM, consistent with findings previously reported by Hu et al [3]. However, we noted the resistance to MTX-211 in cancer cells overexpressing ABCG2 alongside HEK293 cells ectopically expressing human ABCG2 (R482-HEK293), compared to parental HEK293 cells (Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, our objective was to assess the influence of ABCG2 on the anti-proliferative efficacy of MTX-211. We observed that MTX-211 displayed inhibitory effects on cancer cell proliferation across various origins, with IC50 values falling within the range of approximately 1-8 µM, consistent with findings previously reported by Hu et al [3]. However, we noted the resistance to MTX-211 in cancer cells overexpressing ABCG2 alongside HEK293 cells ectopically expressing human ABCG2 (R482-HEK293), compared to parental HEK293 cells (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…The novel EGFR and PI3K dual inhibitor MTX-211 demonstrated promising preclinical activity [2,3]. More importantly, Maust et al highlight the potent growth-inhibitory properties of MTX-211 in BRAF-mutant and KRAS-mutant colorectal cancer models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MTX-211 is a potential antitumor agent that reduces GSH levels through the Keap1/Nrf2/GCLM signaling pathway ( 85 ), thereby effectively inhibits the proliferation of BCa cells. Therefore, regulating the metabolism of GSH through the Nrf2/GCLM signaling pathway may be an effective strategy for treating BCa or overcoming chemotherapy resistance ( 86 , 87 ). Like above-mentioned PC and PCa, in BCa, p62 functions the same model with Nrf2 ( 88 ).…”
Section: Nrf2 In Oncologymentioning
confidence: 99%
“…Similarly, the induction of ferroptosis increases drug sensitivity. In studies on various tumors such as head and neck cancer ( 28 ), pancreatic cancer ( 29 ), hepatocellular carcinoma ( 30 ), and bladder cancer ( 31 ), the induction of ferroptosis through mechanisms such as the regulation of GSH metabolism, lipid metabolism, and redox was found to be an effective strategy for overcoming drug resistance. Ferroptosis is an effective therapeutic approach for targeting CSCs.…”
Section: Introductionmentioning
confidence: 99%